Znaczenie nadzoru właścicielskiego w spółkach z udziałem Skarbu Państwa w systemie corporate governance - Jakub Marchewka (Studia Administracyjne, 2024)
Corporate governance is a complex issue of a practical nature that is of interest to such sciences as law, management, economics and accounting. Corporate governance refers to a system of complementary institutions (legal and economics) to ensure the proper and effective functioning of companies. The purpose of this article is to demonstrate whether corporate governance mechanisms provide the State Treasury with adequate instruments to influence companies with its shareholding. The supervision mechanisms resulting from the regulation contained in the Act on the Principles of State Property Management statute special solutions in relation to the general supervision mechanisms resulting from the Commercial Companies Code. The article uses the formal-dogmatic method.